2015
DOI: 10.3109/00498254.2015.1010633
|View full text |Cite
|
Sign up to set email alerts
|

Improvement bioavailability of silymarin ameliorates severe dyslipidemia associated with metabolic syndrome

Abstract: 1. To compare the effectiveness of different drug forms of silymarin: standardized extract of silymarin (SS), micronized silymarin (MS) and silymarin in the form of phytosome (PS) on dyslipidemia and liver fat accumulation in a model of metabolic syndrome, in non-obese hereditary hypertriglyceridemic rats. The second aim of this study was to slightly uncover the silymarin action on enzymes and proteins involved in cholesterol metabolism and excretion. 2. Silymarin administered to hereditary hypertriglyceridemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…Cholesterol-lowering effect (-16 % or -18 %; p<0.01) was measured in group supplemented with n-3 PUFA without or with SM, respectively, compared to the controls. The hypolipidemic effects of SM are consistent with our earlier findings showing its effects on the reduction of serum TAG concentrations in HHTg rats and dietary-induced hypercholesterolemia (Orolin et al 2007, Poruba et al 2015. We did not test this effect of SM alone again.…”
Section: Parameters Of Antioxidant System and Lipoperoxidationsupporting
confidence: 89%
See 1 more Smart Citation
“…Cholesterol-lowering effect (-16 % or -18 %; p<0.01) was measured in group supplemented with n-3 PUFA without or with SM, respectively, compared to the controls. The hypolipidemic effects of SM are consistent with our earlier findings showing its effects on the reduction of serum TAG concentrations in HHTg rats and dietary-induced hypercholesterolemia (Orolin et al 2007, Poruba et al 2015. We did not test this effect of SM alone again.…”
Section: Parameters Of Antioxidant System and Lipoperoxidationsupporting
confidence: 89%
“…Additionally, hypolipidemic and glucose-lowering properties of SM have been observed as well Krecman 1998, Skottova et al 2003). Recently, it was found that the micronized form of SM provides more pronounced effects than standardized extract, mainly due to its better solubility (Zhang et al 2009, Poruba et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, silymarin increased HDL level, which has an important role in the reverse transport of cholesterol. This study also showed that phytosome and micronized forms of silymarin were the most effective forms because of their better bioavailability (Poruba et al, 2015).…”
Section: Studies On Silymarinmentioning
confidence: 61%
“…In this study, silymarin increased HDL level, which has an important role in the reverse transport of cholesterol. This study also showed that phytosome and micronized forms of silymarin were the most effective forms because of their better bioavailability (Poruba et al, ). Moreover, administration of silymarin and polyphenolic fraction of silymarin significantly decreased cholesterol absorption, the plasma level of cholesterol, liver content of VLDL, and triacylglycerol.…”
Section: Effect On Lipid Profilementioning
confidence: 87%
See 1 more Smart Citation